2020
DOI: 10.3390/foods9111692
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Pecan Shell, Roselle Flower and Red Pepper on the Quality of Beef Patties during Chilled Storage

Abstract: The antioxidant and antimicrobial effects of pecan shell (PSW), combined with roselle flower (RS) and red pepper (CA) were analyzed in beef patties by several methods during chilled storage for 13 days. Additionally, the antioxidant and antimicrobial activities of PSW, RS and CA extracts were determined. The PSW extract exhibited a higher radical scavenging activity (by the DPPH method) and more total phenolic compounds than RS and CA. RS presented the best antimicrobial capacity. Nine formulations of beef pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…In this regard, Hs by-products displayed higher antioxidant properties than oyster mushroom powder. However, the DPPH values (45.83 vs. 98.29 µmol Trolox/g) and phenolic contents (7.00 vs. 15.02 mg GAE/g) obtained in Hs by-products were around half of those reported by Villasante et al [32] in the original roselle plant. These values were also lower than those reported by Borras-Linares et al [33] in the extract obtained from the dried calyxes of several varieties of Mexican roselle (24-100 mg GAE/g, 27.4-112 µmol Trolox/g).…”
Section: Antioxidant Properties Of Pd and Hs Ingredients And Patty Li...mentioning
confidence: 53%
See 1 more Smart Citation
“…In this regard, Hs by-products displayed higher antioxidant properties than oyster mushroom powder. However, the DPPH values (45.83 vs. 98.29 µmol Trolox/g) and phenolic contents (7.00 vs. 15.02 mg GAE/g) obtained in Hs by-products were around half of those reported by Villasante et al [32] in the original roselle plant. These values were also lower than those reported by Borras-Linares et al [33] in the extract obtained from the dried calyxes of several varieties of Mexican roselle (24-100 mg GAE/g, 27.4-112 µmol Trolox/g).…”
Section: Antioxidant Properties Of Pd and Hs Ingredients And Patty Li...mentioning
confidence: 53%
“…The antioxidant properties and polyphenol content of Pd and Hs methanolic extracts are reported in Table 2. Hibiscus calyx has been reported to be rich in bioactive compounds, such as polyphenols, that can exert antioxidant activity [31,32]. In this regard, Hs by-products displayed higher antioxidant properties than oyster mushroom powder.…”
Section: Antioxidant Properties Of Pd and Hs Ingredients And Patty Li...mentioning
confidence: 99%
“…The increase in pH could be due to the degradation of nitrogenous components in beef patties during the storage period. This process was directly influenced by the action of endogenous or microbial enzymes such as proteases or lipases (Danowska-Oziewicz and Kurp, 2017;Morsy et al, 2018;Villasante et al, 2020). Similarly, Ikhlas et al (2012) reported an increase in the pH value in Cosmos caudatus, Polygonum minus, and BHT treated quail meatballs during the refrigeration storage.…”
Section: Sensory Attributes Of Beef Patties With Pennyroyal Powdermentioning
confidence: 91%
“…Similarly, Ikhlas et al (2012) reported an increase in the pH value in Cosmos caudatus, Polygonum minus, and BHT treated quail meatballs during the refrigeration storage. Also, Villasante et al (2020) reported a significant increase in the pH of beef patties including different combinations of pecan shells, rosella flowers, and red pepper during the storage period. As seen in Table 3, the addition of pennyroyal powder showed a significant effect on TBARS of beef patties (P <0.05).…”
Section: Sensory Attributes Of Beef Patties With Pennyroyal Powdermentioning
confidence: 97%
“…The shelf life of the beef patty product incorporated with pecan nut and roselle was not evaluated in the present work. However, pecan nut and roselle are rich in antioxidant and antimicrobial compounds (Alasalvar and Bolling, 2015;Jabeur et al, 2017), the incorporation of which has been demonstrated to extend the shelf life of meat products (Villasante et al, 2020). Phenolics are phytochemical compounds that can inactivate and reduce the formation of free radicals in the body (Parr and Bolwell, 2000).…”
Section: Antioxidant Activity and Total Phenolic Contentmentioning
confidence: 99%